2017
DOI: 10.1038/ncb3590
|View full text |Cite
|
Sign up to set email alerts
|

NFIA co-localizes with PPARγ and transcriptionally controls the brown fat gene program

Abstract: Brown fat dissipates energy as heat and protects against obesity. Here, we identified nuclear factor I-A (NFIA) as a transcriptional regulator of brown fat by a genome-wide open chromatin analysis of murine brown and white fat followed by motif analysis of brown-fat-specific open chromatin regions. NFIA and the master transcriptional regulator of adipogenesis, PPARγ, co-localize at the brown-fat-specific enhancers. Moreover, the binding of NFIA precedes and facilitates the binding of PPARγ, leading to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 52 publications
3
91
1
Order By: Relevance
“…PPARc can be induced before transcription activation of adipocyte genes and plays an important role in adipocyte differentiation [64]. PPARc localizes at the brown-fat-specific enhancers, and the binding of nuclear factor I-A (NFIA) to the brown fat enhancers precedes and facilitates the binding of PPARc, leading to increased chromatin accessibility and active transcription [65]. PPARc can also regulate the mutual transformation between adipocytes and osteoblasts, thereby affecting lipid metabolism, which can promote the differentiation of bone marrow mesenchymal stem cells into adipocytes and inhibit the differentiation into osteoblasts [66].…”
Section: Pparγ In Renal Lipid Metabolismmentioning
confidence: 99%
“…PPARc can be induced before transcription activation of adipocyte genes and plays an important role in adipocyte differentiation [64]. PPARc localizes at the brown-fat-specific enhancers, and the binding of nuclear factor I-A (NFIA) to the brown fat enhancers precedes and facilitates the binding of PPARc, leading to increased chromatin accessibility and active transcription [65]. PPARc can also regulate the mutual transformation between adipocytes and osteoblasts, thereby affecting lipid metabolism, which can promote the differentiation of bone marrow mesenchymal stem cells into adipocytes and inhibit the differentiation into osteoblasts [66].…”
Section: Pparγ In Renal Lipid Metabolismmentioning
confidence: 99%
“…Interestingly, we find a small set of 6-mers with higher weights that classify humandecrease and chimpanzee-increase OCRs, which correspond to NFI binding motifs (Supplemental Table 11). This result is intriguing since NFIA and the master adipogenesis transcription factor PPARG co-localize to regulate adipogenesis in brown adipocytes as well as in white adipocytes transdifferentiating into beige adipocytes (24,25). Since co-localization of NFIA and PPARG motifs is correlated with an increase in brown adipocyte gene expression, we could measure how often NFIA and PPARG binding motifs occur in the same OCR ( Figure 4B).…”
Section: Transcription Factor Binding Motifs Characterize Species-spementioning
confidence: 99%
“…Although histology on frozen adipose samples is challenging, we can still observe evidence of browning from the chromatin landscape. The NFI motif has been implicated in adipogenesis and differences in brown and white tissues (24,25). A recent systems biology comparison of murine brown and white adipose found that open chromatin regions enriched in brown adipose contain the NFI motif and a high enrichment for GO terms involved with browning of fat (24).…”
Section: Humans May Have Lower Beiging Potential Than Chimpanzeesmentioning
confidence: 99%
“…PCSK5 has also been identified as a putative gene associated with feed utilization efficiency, in part owing to its differential expression in the liver of divergent residual feed intake animals (Tizioto et al 2015). NFIA (nuclear factor I-A) is associated with regulating brown adipose tissue gene expression patterns (Hiraike et al 2017;Shapira & Seale 2017), and regulates the differentiation of embryonic articular cartilage (Singh et al 2018).…”
mentioning
confidence: 99%